2015
DOI: 10.1080/19490976.2015.1011876
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial markers are associated with diabetes onset, regulatory imbalance, and IFN-γ level in NOD Mice

Abstract: Gut microbiota regulated imbalances in the host's immune profile seem to be an important factor in the etiology of type 1 diabetes (T1D), and identifying bacterial markers for T1D may therefore be useful in diagnosis and prevention of T1D. The aim of the present study was to investigate the link between the early gut microbiota and immune parameters of non-obese diabetic (NOD) mice in order to select alleged bacterial markers of T1D. Gut microbial composition in feces was analyzed with 454/FLX Titanium (Roche)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 36 publications
19
94
0
Order By: Relevance
“…Association of Bacteroides with diabetes development in different animal models of T1D is less clear. In one study, Bacteroides spp were found to be more abundant in young NOD mice which did not develop diabetes 33. In this study, Bacteroides spp abundance associated with low-diabetes incidence and revealed the presence of species potentially supporting the establishment of immune tolerance in the NOD/MrkTac colony, such as B. fragilis and B. thetaiotaomicron 13 14 17 18 (see also online supplementary discussion).…”
Section: Discussionmentioning
confidence: 53%
“…Association of Bacteroides with diabetes development in different animal models of T1D is less clear. In one study, Bacteroides spp were found to be more abundant in young NOD mice which did not develop diabetes 33. In this study, Bacteroides spp abundance associated with low-diabetes incidence and revealed the presence of species potentially supporting the establishment of immune tolerance in the NOD/MrkTac colony, such as B. fragilis and B. thetaiotaomicron 13 14 17 18 (see also online supplementary discussion).…”
Section: Discussionmentioning
confidence: 53%
“…One relative abundance difference was that S24-7 decreased in the Ex (p<0.05) but not the WM (p=0.2) group. This species has been shown to differ between diabetic and non-diabetic mice (19); thus, this Ex-related shift may be in line with the robust insulin-sensitizing effect of exercise. Opposite to previous observations reported by Kang et al, we observed an increase in the relative abundance of Streptococcus with exercise (17).…”
Section: Discussionmentioning
confidence: 69%
“…The intestinal microbiomes of Eα16/NOD mice showed increased α-diversity, which has been associated with protection from T1D in genetically susceptible mice and humans (25,26). To directly confirm this conclusion, we compared the ability of intestinal microbiota from Eα16/NOD vs. NOD donors to protect NOD recipients from insulitis.…”
Section: Eα16/nod Mice Hosted a Distinct Intestinal Microbiome Early Inmentioning
confidence: 99%